(untitled) (Contemporary Journal of Social Science Review, 2024)
The life of Prophet Muhammad (SAW) has long been the subject of deep scholarly attention within Islamic traditions, producing a vast body of Seerat literature rooted in devotion, theological insight, and historical authenticity. In contrast, Western scholarship has approached the Prophet’s life from multiple academic angles, often shaped by broader ideological, historical, and cultural contexts. This study examines the Western perspectives on Seerat through a focused analysis of the works of Karen Armstrong, one of the most influential and sympathetic Western authors writing about Islam and the Prophet Muhammad (SAW). Her books Muhammad: A Biography of the Prophet (1991) and Muhammad: A Prophet for Our Time (2006) represent a paradigm shift in non-Muslim representations of the Prophet by striving to foster understanding between civilizations and to dispel stereotypes prevalent in the West. This research explores Armstrong’s methodology, sources, and interpretive framework, analyzing how she constructs a narrative of the Prophet that resonates with both Muslim and non-Muslim readers. The study evaluates the impact of her writings on Western discourse surrounding Islam, especially in the post-9/11 world, and the role of such literature in promoting interfaith dialogue and mutual respect. Through comparative textual analysis and critical engagement, this paper assesses the effectiveness and limitations of Armstrong’s contributions within the broader context of Western Seerat writing. The findings underscore the importance of balanced, empathetic scholarship in bridging cultural divides and advancing a nuanced understanding of Islamic history and the life of the Prophet Muhammad (SAW).